1988
DOI: 10.1002/jcp.1041370224
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of dihydropyridines on 45Ca uptake induced by the K+ —channel blocker 4‐aminopyridin on mast cells

Abstract: The 1,4-dihydropyridines (DHP) are calcium antagonists and represent a new class of drugs which act by a selective inhibition of Ca++ influx through voltage-operated calcium channels. We report the effect of nifedipine (Bay A 1040), nisoldipine (Bay K 5552) and nitrendipine (Bay E 5009) on the histamine release and on the 45Ca uptake promoted by 4-aminopyridin in mast cells. These cells treated with DHP (10(-12)-10(-3) M) activated the secretory response in a dose-dependent manner in the range of concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We have previously shown that both pleural and peritoneal mast cells have no specific sodium channel (Vieytes et al, 1991b) and that cation fluxes may take place through common channels (Eleno et al, 1988). Also, the existence of a Na+/K+ pump which contributes to sodium efflux was demonstrated in rat mast cells.…”
mentioning
confidence: 99%
“…We have previously shown that both pleural and peritoneal mast cells have no specific sodium channel (Vieytes et al, 1991b) and that cation fluxes may take place through common channels (Eleno et al, 1988). Also, the existence of a Na+/K+ pump which contributes to sodium efflux was demonstrated in rat mast cells.…”
mentioning
confidence: 99%
“…Ouabain does not cause any appreciable change on the membrane potential confirming that the Na+/K+ ATPase pump is not directly implicated in maintaining the resting potential in these cells (Mohr and Fewtrell, 1987b). RBL cells or basophils appear to be different to many secretory cells, since they fail to secrete when they are depolarized in high potassium medium (Eleno et al, 1988;Mohr and Fewtrell, 1987a).…”
mentioning
confidence: 99%
“…The total activity added to each test tube was 500±30x 103 dpm. The method used has been de scribed previously [7]; briefly, a layer of immersion oil was placed at the bottom of Akes cylindroconical polyethylene tubes (500 pi). A suspension of purified mast cells was carefully decanted onto this layer and incubated for 20 min at 37 °C in BSS without protein.…”
Section: Measurement O F Isca Uptakementioning
confidence: 99%
“…Sensi tized mast cells secrete a wide variety of inflammatory mediators upon cross-linking of plasma membrane IgE receptors. Attempts to determine how mast cell secretion may be regulated have included the identifi cation of several receptors and N a+-, K+-, and Ca2+-specific ionic channels [4,7,12,16,25], How ever, it is not fully understood how the activation of the receptors of IgE initiates the exocytosis. There is little and conflicting information about the electrophysiological properties of mast cells.…”
Section: Introductionmentioning
confidence: 99%